Effect of Rare Earth Metals on Mechanical and Corrosion Properties of Al-Zn-Mg-Cu-Zr Alloy. Issue 8 (August 2017) - Yan, Gao; Wenlin, Chen; Zhen, Guo; Liang, Wang
Abstract: The effect of rare earth metals on mechanical and corrosion properties of 7085 aluminum alloy (Al-7.5Zn-1.5Mg-1.4Cu-0.15Zr) was investigated by means of optical microscopy (OM), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Intergranular, exfoliation corrosion, hardness, tensile test and electrical conductivity test were performed Al alloys on both with and without rare earth additives. Results show the Al alloys with rare earth metals present better mechanical properties such as higher strength and hardness as a result of finer microstructure in comparison with those without the additives. The corrosion resistance is greatly improved by adding rare earth metals. Intergranular corrosion resistance is enhanced from Level IV to Level II, the denudation level for 48 h is improved from EB to PA and I SSRT reflecting stress corrosion resistance was enhanced from 65% to 96%.